Reflection before action: Students’ perceptions of selected aspects of the language teaching profession - Michońska-Stadnik, Anna (Glottodidactica, 2019)
The study explores trainee teachers’ opinions on selected aspects of the language teaching profession. Reflecting on the reasons for becoming a teacher, on a language teacher’s professional qualities, and on the positive and negative aspects of the profession appears to be necessary at the starting point of professional training. A qualitative method was employed to collect the data. The students were asked to answer four survey questions pertaining to the issues mentioned above. Thirty-five undergraduate students completed the survey. Their answers were then analysed, which resulted in suggesting some procedures that could be implemented in the training programme. The findings revealed generally positive attitudes to the language teaching profession. However, some actions should be also taken to eliminate a few subjective theories that could negatively influence the students’ approach, such as the feeling of having power over learners, or controversial ways of dealing with discipline problems in the classroom. The study emphasised the role of reflection in the initial stages of teacher training